2015
DOI: 10.1128/aac.04271-14
|View full text |Cite
|
Sign up to set email alerts
|

The Efflux Pump Inhibitor Timcodar Improves the Potency of Antimycobacterial Agents

Abstract: bPrevious studies indicated that inhibition of efflux pumps augments tuberculosis therapy. In this study, we used timcodar (formerly VX-853) to determine if this efflux pump inhibitor could increase the potency of antituberculosis (anti-TB) drugs against Mycobacterium tuberculosis in in vitro and in vivo combination studies. When used alone, timcodar weakly inhibited M. tuberculosis growth in broth culture (MIC, 19 g/ml); however, it demonstrated synergism in drug combination studies with rifampin, bedaquiline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Therefore, plasma drug concentrations of new drugs such as bedaquiline and delamanid will receive more attention in future studies as well as in daily practice. Also, in cases of off-label use or in studies evaluating the bactericidal activity of drug combinations, information on drug exposure is helpful to explain treatment outcome (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, plasma drug concentrations of new drugs such as bedaquiline and delamanid will receive more attention in future studies as well as in daily practice. Also, in cases of off-label use or in studies evaluating the bactericidal activity of drug combinations, information on drug exposure is helpful to explain treatment outcome (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…The approach of inhibiting transporters in order to overcome drug resistance is currently being applied to the bacterial pathogens Pseudomonas aeruginosa, future science group Targeting efflux pumps to overcome antifungal drug resistance Review Escherichia coli and Mycobacterium tuberculosis [22,23]. For example, the efflux pump inhibitor timcodar has been shown to increase the potency of the antituberculosis drugs rifampin and isoniazid toward M. tuberculosis in both in vitro and in vivo combination studies even though its precise mechanism of action is unknown [24]. The resistance-nodulation-division family of efflux pumps has received particular attention in P. aeruginosa and E. coli [25].…”
Section: Overcoming Drug Efflux As An Adjunct To Drug Discoverymentioning
confidence: 99%
“… 79 These results occur when EPIs act as a single drug such as an SQ109 inhibitor, or enhances the efficacy of certain drug combinations such as timcodar. 80 , 81 More recently, Kumar et al 82 found that synthesis and design of hybrid EPIs by fusion of Verapamil™ with phenothiazines enhances inhibition of efflux pumps and may enable identification of novel molecules with a high efficacy for killing MTB.…”
Section: Development Of Drug-resistant Mtbmentioning
confidence: 99%